Options for middle vault and dorsum restoration after hump removal in primary rhinoplasty - Kovacevic, Milos; Riedel, Frank (Facial plastic surgery, 2016)
Prevention of unfavorable sequelae following humpectomy in reduction rhinoplasty by restoration of the middle nasal vault complex today has become imperative in the majority of patients with perhaps the exception of small humps. In general, the techniques used for preservation and reconstruction of these important anatomical structures can be divided into two main categories: spreader graft and spreader flap techniques. Oversimplified spreader graft techniques require donor cartilage, whereas spreader flap techniques use the excess height of the medial portion of the upper lateral cartilages in patients with a cartilaginous hump. In principle, both donor cartilage and preserved upper lateral cartilages usually are positioned along both sides of the dorsal septum to provide natural and harmonious contours as well as to avoid functional impairment (valve collapse). However, the considerable number of publications on this topic attests to existing downsides of both surgical principles. To overcome these shortcomings, we illustrate additional modifications in the application of spreader grafts as well as spreader flaps. However, the main goal of this article is to provide an algorithm helping to decide which technique is best suited to meet the requirements of each individual patient.